1999
DOI: 10.1364/ol.24.000679
|View full text |Cite
|
Sign up to set email alerts
|

208-W TEM_00 operation of a diode-pumped Nd:YAG rod laser

Abstract: 208-W average-power TEM(00) -mode operation from a diode-pumped Nd:YAG rod laser was demonstrated. The side-pumping method of generating a high-gain aberration-free rod, the bifocusing-compensation technique with two identically pumped rods, and a suitable choice of beam spot size were employed in the design of this laser. At the maximum pump power of 1.1 kW the fundamental transverse-mode operation (M(2)<1.1) was characterized by 7.6% electrical efficiency. The extraction efficiency was almost 60% of full mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(18 citation statements)
references
References 8 publications
0
16
0
2
Order By: Relevance
“…In this way, the output polarization after the rotator is rotated by 901, and the radial and tangential components of the polarization will accumulate the same average phase delay after passing through two rods. Therefore, every spot of the beam in the cross section must pass through the same position in the two birefringent rods, which can be satisfied by a symmetrical resonator [12].…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the output polarization after the rotator is rotated by 901, and the radial and tangential components of the polarization will accumulate the same average phase delay after passing through two rods. Therefore, every spot of the beam in the cross section must pass through the same position in the two birefringent rods, which can be satisfied by a symmetrical resonator [12].…”
Section: Article In Pressmentioning
confidence: 99%
“…By this way, both the beam quality and the power density are improved at the fundamental wavelength, so high PCF can be ensured. Moreover, the laser operates as a thermally near-unstable resonator and compensates thermal birefringence, which also ensures high beam quality [11,12]. The average green output power of 121 W is obtained with pulse width of 68 ns and repetition rate of 10 kHz.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, improving the output power, i.e. the slope efficiency, of a DPSSL is also an important goal in achieving ever-higher power [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have reported high-power green lasers with high beam quality and side-pumped Nd:YAG modules, which are usually obtained by extracavity-frequency-doubling with a complex end-pumped master-oscillator power amplifier (MOPA) system [10−12] or a complex injection seeded system [13] . However, Hirano et al have reported an output power of 208-W TEM 00 1 064-nm laser with two specially designed side-pumped Nd:YAG modules [14] , which has the potential to obtain high-power high-beamquality second harmonic generation (SHG) with a compact intracavity-frequency-doubling system.In this letter, we report a high-power high-beamquality 1 064-nm Nd:YAG rod laser and SHG by intracavity-frequency-doubling. We used a short symmetrical cavity with two concave mirrors compensating for the thermal focal effect of the Nd:YAG rod.…”
mentioning
confidence: 99%
“…Moreover, in comparison with the conventional unstable resonators, the plane-parallel cavity has a wider thermal stability region according to the theoretical calculation with the standard ABCD ray propagation matrix. The configuration of the cavity is demonstrated to have a good scheme for high-power TEM 00 1 064-nm laser generation [14] . With two common side-pumped Nd:YAG rod modules in the short cavity, we achieved an 82.3 W near diffraction-limited continuous wave (CW) 1 064-nm laser (M 2 ≈1.38) with a good power stability of ±1.1% for over two hours.…”
mentioning
confidence: 99%